THE ACTION OF CYTOKINES ANDGROWTH FACTORS IN THE INFLAMMATORY RESPONSE OF THE BODY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cytokines and growth factors are highly potent proteins (active in picomolar concentrations) that exert a wide range of biological effects. Unlike hormones, which maintain homeostatic balance, cytokines and growth factors provide a response to foreign body invasion, immune damage, inflammation, repair and regeneration. They form a network of communication signals between immune system cells and cells of other organs and tissues. These proteins promote inflammation and immune response, but their secretion may be in response to other stimuli (microorganisms, their waste products). In addition to secretion, cytokines can be expressed on the surface of stimulated cells. They bind to specific receptors on target cells [1,2,3].